Tantangan dan Peluang Implementasi Restrukturisasi Birokrasi Dalam Mewujudkan Tata Kelola Pemerintahan yang Baik (Good Governance) di Pemerintahan Daerah Luwu Utara - Saputra, Sakral Wijaya; Latief, Mutmainnah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Background : Regional Governments hold a crucial role in providing public services and fostering regional development. However, along the way, the bureaucrary in many of these governments often faces various challenges. Complex organitation structures, convoluted procedures, a lack of innovative work culturem and the appointment of officials who don’t follow proper mechanisms or lack spesific competence often become major obstacles to creating effective and efficient governance. As a result, the quality of public services is hindered, transparancy isn’t achieved, accountability is hard to reach, and public satisfaction begins to decline. Objective: As one stratrgic solution, restructuring isn’t just a matter of changing names or reorganizing positions. It’s a fundamental transformation aimed at creating a results-oriented bureaucracy. Methods: This research uses a qualitative aproach with in-depth interview technique, focusing on high-level and regular officials. Data was collected through in-depth interviews with key informants and document analysis followed the model of Miles and Huberman, starting with data reduction, wich involves summarizin, selecting, and focusing the data gathered from interviews, observations, and documents Results: Implementing bureaucratic restructuring in the Luwu Utara Regional Government will face major obstacles in achieving good governance. Structural transparant, efficient, and accountable bureaucracy if they are not acoompanied by changes in the culture of official appointments, the work culture, political commitment, and the active involvement of all parties. However, for long-term success, bureaucratic restructuring must be a fundamental part of a comprehensive and suistainable reform, not just an incidental program.